Integrated metabolomics and network toxicology to reveal molecular mechanism of celastrol induced cardiotoxicity - Liu, Chuanxin; Zhang, Chenning; Wang, Wenxin; Yuan, Fuli; He, Tao; Chen, Yahong; Wang, Qiang; Huang, Jianmei (Toxicology and applied pharmacology, 2019)
Celastrol (CS), an active triterpene derived from traditional Chinese medicine Tripterygium wilfordii Hook. f, has been used to treat chronic inflammation, arthritis and other diseases. However, it has been reported that CS can trigger cardiotoxicity and the molecular mechanism of heart injury induced by CS is not clear. Considering the wide application of Tripterygium wilfordii Hook. f in clinics, it is necessary to develop an accurate and reliable method to assess the safety of CS, and to elucidate as much as possible the mechanism of cardiotoxicity induced by CS. In this study, Ultra-performance liquid chromatography coupled with quadrupole time of flight mass spectrometry (UPLC-Q-TOF/MS)-based metabolomics revealed clues to the mechanism of CS-induced heart injury. Palmitic acid significantly increased in plasma from CS-treated rats, and this increase resulted in oxidative stress response in vivo. Excessive ROS further activate TNF signaling pathway and caspase family, which were obtained from the KEGG enrichment analysis of network toxicology strategy. Protein expression level of caspase-3, caspase-8, bax were significantly increased by western blot. Q-PCR also showed the similar results as western blot. It means that apoptosis plays a key role in the process of celastrol induced cardiotoxicity. Blocking this signal axis may be a potential way to protect myocardial tissue. [Display omitted] •Celastrol can induce cardiac injury based on pathological section.•Palmitic acid is a key metabolite that can induce oxidative stress in vivo.•TNF/caspase signal axis plays a key role in CS triggered cardiotoxicity.